The contributions of myelin and axonal caliber to transverse relaxation time in shiverer and neurofilament-deficient mouse models - Dyakin, Victor V. (2010)
White matter disorders can involve injury to myelin or axons but the respective contribution of each to clinical course is difficult to evaluate non-invasively. Here, to develop a paradigm for further investigations of axonal pathology by MRI, we compared two genetic mouse models exhibiting relatively selective axonal or myelin deficits using quantitative MRI relaxography of the transverse relaxation times (T2) in vivo and ultrastructural morphometry. In HM-DKO mice, which lack genes encoding the heavy (NF-H) and medium (NF-M) subunits of neurofilaments, neurofilament content of large myelinated axons of the central nervous system (CNS) is markedly reduced in the absence of changes in myelin thickness and volume. In shiverer mutant mice, which lack functional myelin basic protein, CNS myelin sheath formation is markedly reduced but neurofilament content is normal. We observed increases in T2 in nearly all white matter in Shiverer mice compared to their wild type, while more subtle increases in T2 were observed in HM-DKO in the corpus callosum. White matter T2 was generally greater in Shiverer mice than HM-DKO mice. Ultrastructural morphometry of the corpus callosum, which exhibited the greatest T2 differences, confirmed that total cross sectional area occupied by axons was similar in the two mouse models and that the major ultrastructural differences, determined by morphometry, were an absence of myelin and larger unmyelinated axons in shiverer mice and absence of neurofilaments in HM-DKO mice. Our findings indicate that T2 is strongly influenced by myelination state and axonal volume, while neurofilament structure within the intra-axonal compartment has a lesser effect upon single compartment T2 estimates.